COVID‐19 Infection and Massive Aortic Dissection - Mehrangiz Zangeneh; Yasamin Khosravaninezhad; Masoumeh Mesgarian (Clinical Case Reports)
ABSTRACT COVID‐19 had a significant impact on public health, including respiratory and cardiovascular complications. Because of COVID‐19 hypercoaglupathy effect, it can lead to cardiovascular complications. A 68‐year‐old Iranian male admitted to the infectious diseases department with the diagnosis of COVID‐19 infection. Despite initially stable vital signs and mild symptoms, the patient's condition rapidly deteriorated over the course of several days, with severe respiratory distress and other concerning symptoms. Further investigations revealed evidence of aortic aneurysm or dissection, which was confirmed to be a Stanford type A aortic dissection extending from the aortic root to the abdominal aorta. The available evidence points to a potential association between COVID‐19 infection and aortic dissection, and the need for continue investigations about the pathophysiological mechanisms underlying this relationship.